Product market competition and audit fees: new evidence - Chung, Hanyong; Kim, Jae B. (Managerial Auditing Journal, 2024)
Purpose The purpose of this study is to examine the relation between product market competition and audit fees by using firm-level product market competition measures and mitigating the endogeneity issues. Design/methodology/approach This study uses 12,136 US firms from 2004 and 2019. To ensure the robustness of the main findings, this study uses three firm-level product market competition measures and import trade tariff rate reductions of the USA as a quasi-natural experiment. This study also performs three cross-sectional tests and validation tests. Findings This study demonstrates that there is a negative relation between product market competition and audit fees and establishes a causal relation. Moreover, it reveals that the findings become more pronounced when auditors possess industry-specific expertise, when client firms are younger, and when operating within more homogeneous industries. Additionally, a validation analysis supports the findings. Practical implications This study offers significant insights for regulators by highlighting how product market competition plays a constructive role in overseeing firm management. Originality/value The authors contribute to the existing literature by showing that there is a negative association between product market competition and audit fees after controlling external monitoring mechanisms. The authors also find the causal relation. These findings indicate that competitive pressures originating from product markets exert a significant influence on disciplining a client firm’s management.
Keywords: Audit fees; Audit risk; Business risk; Corporate governance; External auditor; Product market competition; dept.acc; peer-reviewed